Towards an interoperable Public Administration: interpretation and legal analysis of silence as a consequence of not exchanging required information between public - Stringhini, Antonella (Universidad Nacional del Litoral, 2021)
The objective of the paper is to carry out an interpretation and legal analysis of silence as a consequence of not exchanging required information between public bodies, regulated in article 4 of National Decree No. 733/2018 of the Argentine Republic. Specifically, it aims to elucidate the character that should be given to the information that is not exchanged by the required public body.